India Migration Report 2023: Student Migration (India Migration Report, 2024)
The India Migration Report 2023: Student Migration is one of the first books that attempts to comprehensively explore the various nuances of Indian international student migration factoring in multiple factors that influence the migration journey of Indian students. It also looks into other migration stories including internal and international returnees, various impacts of remittances, and migration in the context of the pandemic. This volume: Inspect the factors driving the student migration from India, accounting for both the historical and current happenings influencing these factors. Following the pandemic, the book highlights the challenges faced by Indian international students in accessing health care and other related services which goes on to push them into vulnerable situations Outlines the reasoning behind Indian students' decision to emigrate and how families play an important role in influencing key migration decisions made by students and the different patterns of student migration observed in India Examines the employment challenges experienced, particularly following the COVID-19 pandemic, by the highly skilled Indian migrants and Indian international students Describes the role that recruitment and consultancy agencies play in international student mobility (ISM) and examines the intricate relationship between migrant agencies and migration facilitation Investigates the psychological, economic and social challenges faced by Indian international students during their migration journey both during and after the completion of their course abroad Provides a critical overview of the conditions of both internal and international returnees to different parts of India Studies the impact of remittances on migrant households including their consumption patterns and human capital investment Analyses interstate migration networks through the prism of gender and critically assesses how gender migration patterns have altered throughout time Scholars, students, researchers, academicians, policymakers or anyone with an interest in migration, migration politics, economics, social psychology, migration policies, development studies, sociology, social anthropology and gender studies will find this book on Indian student migration extremely informative. The book is a comprehensive collection of various studies that look into the multiple aspects of student migration but also extend to other pertinent issues of Indian migration that are extremely relevant at this given point in time.